Five energy metabolism pathways show distinct regional distributions and lifespan trajectories in the human brain - Pourmajidian, Moohebat; Hansen, Justine Y.; Shafiei, Golia; Misic, Bratislav; Dagher, Alain (PLOS Biology, 2026)
Energy metabolism involves the activity of distinct biochemical processes that are key for cellular function, but their distribution across cortex is poorly understood. This study maps five energy metabolism pathways in the human brain, linking metabolic organization with brain structural and functional properties, as well as developmental dynamics.